2009
DOI: 10.1111/j.1600-0714.2009.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase 7 and perlecan in oral epithelial dysplasia and carcinoma in situ: an aid for histopathologic recognition of their cell proliferation centers

Abstract: These results suggest that the enhanced metabolism of perlecan associated with MMP-7 plays an important role in the cell proliferation of oral epithelia in their malignant transformation process, and that MMP-7 immunohistochemistry may be a valuable aid for identification of the cell proliferation center in oral CIS and dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…We previously reported that perlecan, a heparan sulfate proteoglycan of the basement membrane, as well as its lyase MMP-7 accumulated more frequently within the intercellular spaces of advanced grades of (true) epithelial dysplasia and CIS [10,11] . The extension of perlecan and MMP-7 immunopositivity seems to be similar to that of podoplanin, which may indicate that carcinoma cells are in active communication with the extracellular milieu within the zone circumscribed by the basement membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that perlecan, a heparan sulfate proteoglycan of the basement membrane, as well as its lyase MMP-7 accumulated more frequently within the intercellular spaces of advanced grades of (true) epithelial dysplasia and CIS [10,11] . The extension of perlecan and MMP-7 immunopositivity seems to be similar to that of podoplanin, which may indicate that carcinoma cells are in active communication with the extracellular milieu within the zone circumscribed by the basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…However, the difficulties associated with making objective diagnoses of oral precancerous lesions based solely on HEstained sections are much better understood, and a number of studies have been performed to examine objective aids for such diagnoses that are applicable in daily clinical practice. For example, recent immunohistochemical studies have reported the significance of recognition of cellular differentiation (keratins) [6,7] , cell adhesion (Ecadherin and integrins) [8,9] , the intraepithelial extracellular matrix (perlecan) [10] , and their lyases (MMP-7) [11] .…”
Section: Introductionmentioning
confidence: 99%
“…The lower half basaloid cells are Ki-67-positive, and they lack E-cadherin due to hypermethylation of its gene promoter region but show nuclear translocation of β-catenin [11]. In addition, an intercellular deposit of perlecan [12,13] with enhanced expression levels of MMP-7 [13], podoplanin [7], or Wnt target molecules [11] has been demonstrated in the lower half of two-phase dysplasia. Based on these lines of evidence, it is now possible to clearly separate CIS from epithelial dysplasia.…”
Section: Introductionmentioning
confidence: 95%
“…We have also demonstrated the genetic mechanism for the loss of K13 as well as the reciprocal loss of K13 and emergence of K16/ K17 in oral CIS [5,6]. To consolidate our diagnostic criteria of oral CIS, we have introduced some other immunohistochemistry for podoplanin [7,8], perlecan [9][10][11][12], matrix metalloproteinase (MMP) 7 [10], tenascin [12], and β-catenin/E-cadherin [11] as diagnostic aids. More recently, we have also emphasized the formation of intraepithelial blood vessels as one of the histopathologic characteristics of oral CIS and as a driving force for dyskeratosis among cancer cells [13].…”
Section: Introductionmentioning
confidence: 96%